Sociolinguistic Dynamics in Bondowoso: Exploring the Influence of Madurese on Javanese Language Shift - Muhammad Roda’i; Fina Amalia Masri; La Ino; Nanda Saputra; Derysmono; Muta’allim (Attractive : Innovative Education Journal, 2025)
This study explores sociolinguistic dynamics in Bondowoso, East Java, with a focus on the influence of ML on the shift of JL. The data in this study are vocabulary, grammar, and pronunciation that have not yet and have undergone a shift, while its data sources are the language of the community in the Bondowoso environment. Data were collected through survey methods, in-depth interviews, and participatory observations supplemented with recording and note-taking techniques. The researcher conducted interviews with the Bondowoso community regarding the influence of ML on the shift of JL in Bondowoso. The collected data in the form of recordings were then written in the form of orthographic transcriptions. After that, the researcher classified and validated the data based on its categories. The results showed that there were 1) JL that has not experienced diaspora; 2) code-mixing from JL to ML; 3) a shift from JL to ML; and 4) changes in grammar and phonology. The factors influencing the language shift in Bondowoso are 1) Bondowoso is dominated by the MC; 2) migration factor of the MC to Bondowoso; and (3) Primordialism of the Ethnic MC in Bondowoso.